Sosiolinguistik Di Era Digital: Analisis Penggunaan Campur Kode Dalam Sebuah Komunikasi Di Chat Whatsapp (International Forum of Researchers and Lecturers, 2024)
In the era of globalization, technology is developing rapidly, especially in the field of communication media, making the world feel more connected. Internet media, as a rapidly developing communication medium, has penetrated into various levels of society, becoming a necessity in daily activities. Social media networks such as Twitter, Facebook, SMS, BBM, Line, and WhatsApp (WA) have become the main means of delivering various information services. Through this social media network, public communication becomes easier and faster, creating a high level of usage among the public. WhatsApp (WA), as a popular social media service, is used effectively to share information both privately and publicly, not only by teenagers but also by adults. One of them is a WA group which is formed based on needs. For example, the Independent Student Exchange 3 (PMM3) group. Research on code mixing in the use of Indonesian on WhatsApp social media is based on Applied Sociolinguistic Theory.